HUBUNGAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA SMP PADA MATERI SEGITIGA SEGIEMPAT - Usep Rahayu Mulyana; Aflich Yusnita Fitrianna (IKIP Siliwangi, 2019)
The study was conducted to analyze the relationship of learning motivation to the mathematical problem solving ability of 7th grade students. The research method is correlation. The research subjects consisted of 32 7th grade students at SMPN 3 Purwakarta. Test test instruments and non-test instruments are the methods used in data collection. The test given was in the form of 5 problem solving abilities in the form of essays and non-learning motivation scale with Likert scale. The normality test, the correlation test, the determinant coefficient, the significance test to see the correlation between the variables of learning motivation and the variables of mathematical problem solving ability are the steps taken. The conclusion from the results of the study there are 12.18% the relationship between learning motivation and problem solving abilities of junior high school students.